2021
DOI: 10.1002/cpe.6570
|View full text |Cite
|
Sign up to set email alerts
|

FPGA‐based HPC accelerators: An evaluation on performance and energy efficiency

Abstract: Hardware specialization is a promising direction for the future of digital computing. Reconfigurable technologies enable hardware specialization with modest non‐recurring engineering cost, but their performance and energy efficiency compared to state‐of‐the‐art processor architectures remain an open question. In this article, we use FPGAs to evaluate the benefits of building specialized hardware for numerical kernels found in scientific applications. In order to properly evaluate performance, we not only compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Future work activities will be also oriented to test the proposed approach by porting larger and complex Fortran code to the FPGA devices (including AMD/Xilinx ones), as well as to test the synthesized kernels with larger (real) datasets that may provide more chances of making emerge the advantages of the hardware acceleration [14,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work activities will be also oriented to test the proposed approach by porting larger and complex Fortran code to the FPGA devices (including AMD/Xilinx ones), as well as to test the synthesized kernels with larger (real) datasets that may provide more chances of making emerge the advantages of the hardware acceleration [14,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Computer architecture specialization has been established as the main driving factor for achieving better performance and energy efficiency in the current and upcoming high-performance machines. The viability of spatial architectures (and more specifically FPGAs) as mainstream hardware accelerators for computationally highdemanding applications has been already demonstrated by far, with some notable examples in the literature [14]. For instance, [15] analyzed algorithms largely used in the HPC context and found that 5 out of the 13 analyzed were suitable for being accelerated on FPGA devices, although the required knowledge for their porting clearly shows the need for a higher abstraction level.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, there arises a necessity to implement filtering techniques through hardware programming languages in order to uncover more significant accomplishments. Moreover, FPGA is garnering attention and emerging as a potentially energy-efficient platform candidate [50,51]. It demands less power and is commonly embedded within compact systems with limited memory capacity.…”
Section: Related Workmentioning
confidence: 99%
“…Nguyen et al assess the performance of reconfigurable architectures for numerical simulations. 19 They evaluate the performance of FPGAs from Intel and Xilinx, and compare them to the Xeon, Xeon Phi and NVIDIA V100 architectures. Their work shows that while FPGAs typically struggle to compete in absolute terms, they require significantly less power, and can deliver nearly equivalent energy efficiency.…”
Section: Concurrency and Computation: Practice And Experiencementioning
confidence: 99%
“…Nguyen et al assess the performance of reconfigurable architectures for numerical simulations 19 . They evaluate the performance of FPGAs from Intel and Xilinx, and compare them to the Xeon, Xeon Phi and NVIDIA V100 architectures.…”
Section: Performance Modeling Benchmarking and Simulationmentioning
confidence: 99%